Mutations in Two Paraburkholderia phymatum Type VI Secretion Systems Cause Reduced Fitness in Interbacterial Competition - de Campos, Samanta Bolzan; Lardi, Martina; Gandolfi, Alessia; Eberl, Leo; Pessi, Gabriella (Frontiers in Microbiology, 2017)
Paraburkholderia phymatum is a highly effective microsymbiont of Mimosa spp. and has also been shown to nodulate papilionoid legumes. P. phymatum was found to be highly competitive both in a natural environment as well as under controlled test conditions and is more competitive for nodulation over other α− and β-rhizobial strains in a variety of different plant hosts. In order to elucidate the factors that make this bacterium highly competitive for legume infection, we here characterized the type VI secretion system (T6SS) clusters of P. phymatum. T6SSs have been shown to function as a contact-dependent injection system for both bacterial and eukaryotic cells. We identified two T6SS clusters in the genome, created respective mutant strains and showed that they are defective in biofilm formation and in interbacterial competition in vitro. While the T6SS mutants were as efficient as the wild type in nodulating the non-cognate host Vigna unguiculata, the mutants were less competitive in in planta competition assays, suggesting that the T6SS is one of the factors responsible for the success of P. phymatum in infecting legumes by directly inhibiting competitors.